2012
DOI: 10.1620/tjem.227.13
|View full text |Cite
|
Sign up to set email alerts
|

Remobilization Does Not Restore Immobilization-Induced Adhesion of Capsule and Restricted Joint Motion in Rat Knee Joints

Abstract: Joint immobilization, which is used in orthopaedic treatments and observed in bedridden people, usually causes restricted joint motion. Decreased joint motion diminishes activities of daily living and increases burden of nursing-care. The purpose of this study was to clarify the reversibility of immobilization-induced capsular changes and restricted joint motion in rat knee joints. The unilateral knee joints of adult male rats were immobilized with an internal fixator for 1, 2, 4, 8, and 16 weeks as a model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…The room temperature and humidity were maintained at 18°C and 50-55%, respectively. Knee stiffness on the experimental side developed as the animals were kept in their cages for 4 weeks post-surgery [10]. The femorotibial wire was removed in a second surgery at the end of 4 weeks of immobilisation under the same anaesthesia described above.…”
Section: Animal Modelmentioning
confidence: 99%
“…The room temperature and humidity were maintained at 18°C and 50-55%, respectively. Knee stiffness on the experimental side developed as the animals were kept in their cages for 4 weeks post-surgery [10]. The femorotibial wire was removed in a second surgery at the end of 4 weeks of immobilisation under the same anaesthesia described above.…”
Section: Animal Modelmentioning
confidence: 99%
“…Common symptoms of these nervous injuries include dormancy, paresthesia, weakness and atrophy of the effector muscles, as well as the impairment of the normal functions and movements of the lower limbs, since this musculature affects the motricity of the joints 3, 4 , including the ankle, which is responsible for providing a stable base of support for the body, in addition to effectively propelling it during locomotion 5 . Thus, nerve lesions lead to the disuse of the limb and, as a consequence, there is a reduction in the mechanical stimulus necessary to maintain the morphological properties of the joint [6][7][8][9] , which can lead to rigidity of the joint capsule and consequent restriction in movement 10 , as well as atrophic changes in the articular cartilage with a reduction in its thickness and the number of chondrocytes 11,12 . Moreover, according to Hui, McCarty, Masuda, Firestein, Sah 13 , the composition and function of synovial fluid are also altered in cases of joint injury or disease.…”
Section: Introductionmentioning
confidence: 99%
“…Loading and movement of the joint are of major importance for the maintenance of the morphologic and functional integrity of the articular cartilage [27]. Immobilisation of joint comprises a major component of treatment for various diseases whether for the purpose of stabilising fracture frequency or to rest inflamed or damaged tissues secondary to disease or traumatic injury [2,4,28]. The impact of immobilisation and unloading of joints on articular cartilage has been investigated in animal models [2,11] and humans [12,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Immobilisation of joint comprises a major component of treatment for various diseases whether for the purpose of stabilising fracture frequency or to rest inflamed or damaged tissues secondary to disease or traumatic injury [2,4,28]. The impact of immobilisation and unloading of joints on articular cartilage has been investigated in animal models [2,11] and humans [12,27,28]. Previous studies have demonstrated that joint immobilisation and unloading lead to functional adaptation of articular cartilage that involve morphologic changes of chondrocytes and cartilage matrix [13,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation